Effect of Glucosamine and Ascorbic Acid Addition on Beef Burger Textural and Sensory Attributes - Philip Soladoye; Yuliya Hrynets; Mirko Betti; Zeb Pietrasik (Polish Journal of Food and Nutrition Sciences)
Aside from the possible health benefit of dietary consumption of glucosamine (GlcN), studies have also reported its flavour enhancing properties in varying food products. However, the impact of its inclusion on other quality attributes of meat products has been under-assessed. The present study examined the effect of the addition of ascorbic acid (0.1%) and varying levels of GlcN (0.75, 1.5 and 3.0%) on colour stability, textural as well as sensory attributes of beef burger. Except for L * (lightness) value, significant interaction ( p <0.01) between storage time and added ingredient was observed for all colour parameters ( a* ; redness, b* ; yellowness, chroma, and hue angle) in beef burger. Generally, although ascorbic acid preserved the colour attributes of beef burgers during storage, addition of GlcN resulted in the deterioration of these colour parameters. Whereas the present result did not confirm any flavour enhancing attributes of GlcN compared to control, GlcN improved beef burger’s yield and reduced product cook loss. However, level of GlcN above 1.5% resulted in significant flavour and textural deterioration (p<0.05), leading to decline in consumer acceptability of beef burger. This study showed that a moderate level of glucosamine could be used in meat products as a functional ingredient with some additional technological benefits and limited impact on sensory attributes. Ascorbic acid adequately protected the colour of beef burger during refrigerated storage.